(1011) The Impact of Small and Large Numbers of Children on the Health and Welfare of Individual Families: A Micro Case Study تأثير الأعداد الصغيرة والكبيرة من الأطفال على صحة ورفاهية افراد الاسرة: دراسة حالة مصغرة - Wafic Ashraf Hassona. (INP., 2020)
The aim of this paper and the aim of other micro studies for this conference is to provide some new factual. Insights into the under-standing of the relationship of family size, goals, and achievements to family aspirations and general welfare. It is hoped that such factual data can be used as the basis for improving the various educational and informational promoting the concept and practices of family limitation